2012
DOI: 10.1007/s10646-012-0881-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in organochlorine accumulation accompanying life history in the catadromous eel Anguilla japonica and the marine eel Conger myriaster

Abstract: In order to examine the ecological risk for organic pollutants in diadromous fish migrating between sea and freshwater, organochlorine compounds (OCs) were determined in the catadromous eel Anguilla japonica having marine, estuarine and freshwater residence life histories. The eels were collected in Japanese coastal areas. We also compared the OCs accumulation with the marine eel Conger myriaster, which has a similar life history as A. japonica in the marine environment. The ontogenic changes in the otolith st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Evidently the growth phase in continental freshwater and coastal systems is the decisive phase for the uptake of contaminants during the eel's life cycle. These findings are in agreement with results from similar studies (Tapie et al 2011;Arai and Takeda 2012;Byer et al 2013;Sühring et al 2013;Blanchet-Letrouvé et al 2014). Congener patterns of yellow and silver eels from the same habitat in this study showed no significant differences.…”
Section: Instrumental Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Evidently the growth phase in continental freshwater and coastal systems is the decisive phase for the uptake of contaminants during the eel's life cycle. These findings are in agreement with results from similar studies (Tapie et al 2011;Arai and Takeda 2012;Byer et al 2013;Sühring et al 2013;Blanchet-Letrouvé et al 2014). Congener patterns of yellow and silver eels from the same habitat in this study showed no significant differences.…”
Section: Instrumental Analysissupporting
confidence: 93%
“…In a Portuguese study by Guimaráes et al (2009), results indicated that yellow eels originating from stronger polluted habitats showed higher adverse physiological effects determinant for their survival and performance than yellow eels originating from a less polluted habitat. In another study on Japanese eels (Anguilla japonica) by Arai and Takeda (2012) from Japan, the authors state that the ecological risks of organochlorine compounds (OC) increase as the freshwater residence period in eel become longer. Therefore individual lipid contents and migratory histories directly affect the accumulation of those OCs in anguillid eels.…”
Section: Introductionmentioning
confidence: 99%
“…Only in areas with very low environmental impacts (such as Norway, Holmqvist et al, 2006; and Scotland, Oliver et al, 2015) can eels be expected to exhibit low pollutant burdens (Bourillon et al, 2020). Despite the extensive literature on A. rostrata and A. anguilla , there are still only a few studies on the chemical contamination of other species of eels (Arai et al, 2012; Arai & Takeda, 2012; Calvi et al, 2006; Holmqvist et al, 2006; Khalil et al, 2017; Le et al, 2010; Ohji et al, 2006; Redmayne et al, 2000; Yamamuro et al, 2019).…”
Section: Resultsmentioning
confidence: 99%